Pertanggungjawaban Hukum Afiliator Shopee terhadap Iklan Produk Yang Merugikan Konsumen Menurut Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen - Ilmi, Rauzatul; J, Jamhir; Fithria, Nurul (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study analyzes the legal liability of Shopee affiliates in product promotions that have the potential to violate consumer protection based on Law Number 8 of 1999 concerning Consumer Protection (UUPK). The method used is empirical juridical with a statutory and empirical approach, through interviews with affiliates and consumers who use the Shopee Affiliate program in Banda Aceh City. The results of the study indicate that affiliates who gain profits from promotional activities can be qualified as business actors as referred to in Article 1 number (3) of the UUPK, so they are required to provide correct, clear, and honest information as regulated in Article 7 letter b of the UUPK. The actions of affiliates who carry out misleading promotions, make false testimonials, or market products without a distribution permit violate Article 8 and Article 9 of the UUPK and can be categorized as unlawful acts based on Article 1365 of the Civil Code. Consumer protection implemented by Shopee through a refund mechanism is considered quite effective at the dispute resolution stage, but is not optimal in preventing violations due to weak supervision of affiliates. Thus, there is a gap between legal norms (das sollen) and field practice (das sein), so that it is necessary to strengthen regulations and preventative supervision of the digital affiliate system.